Digital Inclusion and Social Justice in the Modern Society: the Role of Public-Private Partnerships - Dielini, Maryna; Alekseieva, Kateryna; Dergach, Anna (Skhid, 2026)
The article examines the prerequisites and relevance of the emergence of digital inclusion and social equality. The main opportunities that digitalization provides for various interested groups including society in general are indicated creating the basis for digital inclusion in society. Digital inclusion is considered as the ability to consume digital services due to their accessibility and the corresponding level of digital literacy. It is noted that the reverse process of digital inclusion is the digital divide which is characterized as uneven access to the Internet and digital tools, differences in digital literacy and infrastructural limitations in access to various digital opportunities. All this causes a digital divide, social inequality, and does not allow creating conditions for social justice. While digital inclusion provides opportunities for different segments of the population to fully participate in the labor market, gain knowledge and master skills, regardless of age and profession, increase the efficiency of production, business and management processes through their automation and robotization, etc. The development of digital inclusion and social justice is facilitated by the creation of public-private partnerships (PPPs) which we define as cooperation between public and private bodies to improve the quality of life of the population and increase the level of well-being. The directions of PPP digitalization and the consequences that it has for the population and the state as a whole are identified. It is noted that PPP plays a significant role in the development of an inclusive society and social justice as it achieves a significant social effect for society. This is justified, among other things, by the opportunities that PPP provides in the development of digital public infrastructure, namely the expansion of Internet accessibility, the development of payment systems, personal identification, etc. PPPs can also focus on the implementation of public services that become possible for implementation with financial, technical or expert support from the private sector. One of the greatest values of PPPs is in the development of digital educational projects or providing remote access to educational platforms. This increases digital inclusion and contributes to a more equitable social distribution.